Follow-up investigation of 12 proposed linkage regions in multiple sclerosis. - Herrera, B; Cader, M; Dyment, D; Bell, J; Ramagopalan, S; Lincoln, MR; Orton, S; Chao, M; Sadovnick, A; Ebers, G (2006)
Multiple sclerosis (MS) is an autoimmune disease with overwhelming evidence for genetic determination, and for which a maternal parent-of-origin effect has been reported. As with many complex diseases, multiple suggestive linkage signals have been observed. However, the only unambiguous association and linkage identified to date is with alleles of the human lymphocyte antigen (HLA) class II region. We have now carried out high-density microsatellite genotyping for 12 of the most promising regions (1p, 1q, 2q, 4q, 5p, 9q, 10p, 11p, 12q, 17q, 18p, 19p) from a whole-genome scan in 552 affected sibling pairs. This has been carried out in 194 families containing avuncular pairs. These permit examination of parent-of-origin effects in non-colineal pairs when divided into likely maternal and paternal trait transmission. The results do not confirm any non-major histocompatibility complex linkage in the overall subset nor in the maternal, paternal or HLA-DRB1*1501 subsets. We were able to establish exclusion for a locus with lambda(AV) > or = 1.3 for all the previously suggested regions. These results again raise the possibility that the paradigm of multiple genes of small individual effect used to justify genome searches in MS is incorrect.